Case Report of Drug Rash with Eosinophilia and Systemic Symptoms Demonstrating Human Herpesvirus‐6 Reactivation. Issue 5 (10th September 2013) - Ferrero, Natalie A.; Pearson, Kelly C.; Zedek, Daniel C.; Morrell, Dean S.
Abstract Drug rash with eosinophilia and systemic symptoms (DRESS) is a severe drug‐induced hypersensitivity syndrome that presents with diffuse cutaneous eruptions, fever, and multiorgan involvement. Here we present a pediatric case of DRESS complicated by human herpesvirus (HHV)‐6 reactivation. After 1 week of sulfasalazine, our patient developed a diffuse morbilliform eruption. Sulfasalazine was discontinued. The patient presented to the emergency department soon thereafter with worsening eruption, fever, rigors, facial edema, and lymphadenopathy. Methylprednisolone was initiated. Peripheral smear did not demonstrate eosinophilia but showed toxic granulation with atypical lymphocytes. Transaminase levels and white blood cell count quickly became elevated, with increased eosinophils, suggesting DRESS. During the methylprednisolone taper, our patient experienced symptom exacerbation, acute hepatitis, and HHV‐6 seroconversion, indicating HHV‐6 reactivation as the cause. As demonstrated by our patient, a decelerated methylprednisone taper is important because of potential symptom flaring during taper. Additionally, in the care of individuals with DRESS, HHV‐6 is often tested for upon admission and not repeated. Delay in the rise of titers necessitates repeat testing.